Menimbang Kembali Pendekatan Kajian Keislaman di Perguruan Tinggi Agama Islam - Syamsun Ni'am (IAIN Ponorogo, 2011)
Insight on the progress of the PTAI (Institute of Islamic Studies) in Indonesia so far involves many things; the disorder of epistemological basis of the PTAI, the direction of global policy in structuring the curriculum, the recruitment of stakeholders, then standardization of the quality of graduates, and institutional holder. One thing that seems to be the consensus among observers is the lack of quality of PTAI’s graduates. However, so far there is no consensus among the thinkers, policy makers as well as the PTAI’s functionaries about how to solve this problem. In the midst of diversity discourse about it, stood out a solution that is much in demand by PTAI’s functionaries, namely the transition of institutional status, from the STAIN to the IAIN, and over from the IAIN to UIN. This paper tries to trace the historical roots of the founding the PTAI in Indonesia to find their main tasks. Results of the search was used as a foothold to reflect on the PTAI’s performance today. This paper finds that since their establishment, Islamic higher education institutions is to bring two tasks, namely as a religious institution and as a scientific institution. In the course of history, sometimes these two tasks go hand in hand, but often both were at opposite position. At one point, Islamic studies at the PTAI took the tendency of normative idealistic-theological approach abandoning the academic approach. Then in the last few decades came the openness, which presented the empirical and academic study of Islam. This paper concludes that the transformation or institutional reform of the PTAI’s status is not the answer to the problem of Islamic studies, but the more important is realignment of the structure of sciences in the PTAI which is the foundation for the interdisciplinary study on Islamic dogmas. The quality of graduates is expected to be flown with a firm decision, whether PTAI will be academic, preaching, or practical-pragmatic interests institutions.